2016
DOI: 10.1371/journal.pone.0166072
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Serum Uric Acid and the Remission of Non-Alcoholic Fatty Liver Disease in Chinese Males

Abstract: Epidemiological studies suggest that higher serum uric acid (sUA) level is significantly associated with nonalcoholic fatty liver disease (NAFLD) development. However, little information is available on the relationships between sUA and NAFLD remission. In the present study, 841 NAFLD males (30–75 years) were recruited from a Chinese prospective cohort study (PMMJS) and followed up for five years. The baseline sUA levels of participants were categorized into four quartiles: 191 μmol/L≤ sUA ≤ 347 μmol/L, 347 μm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…They discovered the increased morbidity of metabolic syndrome and NAFLD accompanied with the increased SUA. In addition, Zhou et al (21) found the higher of the SUA level the lower the probability to attenuate the progression. There was not some mechanism studies, and as an antioxidant, uric acid was rarely researched.…”
Section: Discussionmentioning
confidence: 99%
“…They discovered the increased morbidity of metabolic syndrome and NAFLD accompanied with the increased SUA. In addition, Zhou et al (21) found the higher of the SUA level the lower the probability to attenuate the progression. There was not some mechanism studies, and as an antioxidant, uric acid was rarely researched.…”
Section: Discussionmentioning
confidence: 99%
“…However, the regression of NAFLD is not entirely dependent on weight loss. For instance, one study found that serum uric acid levels were associated with NAFLD remission in Chinese males 19 . In addition, Korean data implied that moderate-to-vigorous exercise is beneficial for improving the resolution of an existing fatty liver regardless of BMI changes during the follow-up period 20 .…”
Section: Discussionmentioning
confidence: 99%
“…In a cross-sectional study including 129 children and adolescents, the association between SUA and NAFLD was not observed (18). In a Chinese prospective cohort study (PMMJS) among 841 NAFLD males, they arrived to the conclusion that the level of SUA was negatively correlated with the remission rate of NAFLD (19). A cross-sectional study of 541 patients with type 2 diabetes showed that the association between SUA and NAFLD was found only in males, but not in females (20).…”
Section: Introductionmentioning
confidence: 97%